Understanding the nature of learners' out-of-class language learning experience with technology. Issue 1 (2nd January 2018) - Lai, Chun; Hu, Xiao; Lyu, Boning
ABSTRACT: Out-of-class learning with technology comprises an essential context of second language development. Understanding the nature of out-of-class language learning with technology is the initial step towards safeguarding its quality. This study examined the types of learning experiences that language learners engaged in outside the classroom and the influencing factors. Three distinct types of technological experiences, with different incentives and different emotional and behavioral manifestations, were identified based on the interview responses of 21 university foreign language learners. Structural equation modeling analysis of 439 survey responses indicated that the three types of technological experiences were influenced differently by various attitudinal and support factors. Instruction-oriented technological experiences were influenced the most by learners' perception of the usefulness of the technological experience for language learning, and entertainment- and information-oriented technological experiences were the only technological experiences that were influenced directly by perceived ease of the technological experience for language learning. Social-oriented technological experiences were influenced by myriad factors. Furthermore, it was found that the influencing factors for these experiences varied for learners with beginning and with intermediate proficiency levels. The findings underscore the importance of adopting differentiated approaches to supporting different types of technological experiences.